Georgia Architectural and Historic Properties Survey of Unknown [4], Sycamore, Turner County, Ga., 1981 - Barton and Harbin (South Georgia Area Planning and Development Commission, 1981)
Georgia Architectural and Historic Properties Survey of Unknown [4], Sycamore, Turner County, Ga., 1981. L-shaped house plan with gabled roof. Shed porch supported by square posts. Shiplap siding. Double sash windows with 4/4 lights. Also aluminum double sash windows. Brick piers, filled with stone and concrete block. Poor to fair condition. Date of Construction: c. 1910. Not significant as part of a potential National Register historic district. Area of older structures not extensive enough.
Georgia Architectural and Historic Properties Survey of Unknown [4], Sycamore, Turner County, Ga., 1981. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 31.6 MB (33,219,452 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Sycamore (Ga.); Turner County (Ga.)